SARS-CoV-2 variants: implications for immunity and vaccine development - Altmann, Danny (Henry Stewart Talks, 2021)
Research into the emergence of SARS-CoV-2 variants with immune escape mutations, The frequencies of immune escape mutations in SARS-CoV-2 and their implications, Potential future scenarios regarding new variants, Potential action plans and available tools for responding to new immune-evading variants.